Revista Focusolar: jornalismo científico, energia renovável e sociedade. - Cunha, Andréa Mesquita de Mendonça (2016)
The present work has as main objective the creation of a pilot magazine, developed along with the Graduate Program in Journalism, named "FocuSolar", in print, on the subject of renewable energy, its sustainability and renewal of strategies in newspaper language, aiming to spread the academic-scientific production of the Center for Alternative and Renewable Energy - CEAR UFPB, placing it as a vehicle to facilitate the understanding of scientific information by widely-varied audiences. Specific objectives include: make CEAR's scientific, academic production become understood by general public; encourage the readers to access scientific knowledge produced by CEAR; contribute to public awareness on the need to adopt more efficient and rational methods and practices when using natural resources; strengthen links between CEAR actions and the journalism field in UFPB; exert a clearing function on the use of renewable energy and its social, environmental and economic implications to general public. The methodological procedures which have guided the choice of theme and language to be used in the product will be divided into seven (7) steps, as follows: definition of the state-of-the-art; knowledge mapping about CEAR academic community; observations about the knowledge structure internally generated by Center members; formatting, technical detailing, planning, and its publishing processes; select scientific articles for a zero issue and the production of content for the magazine layout. The report presents the theoretical foundation, addressing two pathways to reflection: Science journalism and its magazine format, concepts, objectives and functions; and as a second axis, inform renewable energy concepts, presenting its legal framework and the creation of CEAR. The last report version submitted for qualifying exam contains a detailed description of the product, "FocuSolar" magazine, from the stages of survey sources, process planning, publishing, with a pilot issue to be printed. The project adopted as innovation and prospection stance, alliances with undergraduate and journalism graduate courses, creating a product that can serve as a link between academia and society, contributing to the achievement of social inclusion and access to scientific knowledge as a vehicle to facilitate the communication of science to a heterogeneous audience.